O Cadastro Único e a organizaç\~ao de políticas públicas para a implementaç\~ao dos direitos sociais dos povos indígenas - Frederico Augusto Barbosa ds Silva; Isabella Cristina Lunelli; Fabiano Oliveira Souto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The Single Registry for Social Programs of the Federal Government (Cadastro Único) was created in December 2001 and has become a central instrument of public policy, first for the Bolsa Família Program (PBF) and later serving to articulate and integrate numerous other actions, both federal and from other spheres of government. The information from Cadastro Único for Indigenous Peoples is valuable and allows for the establishment of important knowledge about some of the characteristics of the indigenous population and of each people in a singular way, as well as strategies for the protection and promotion of Indigenous Peoples. However, the uses, interpretation, and communication of the data should be the subject of intense debate. The ordinary and familiar discourse of common sense, including internalized and used by public managers, uncritically produces, and reproduces a typical vocabulary and jargon about a generic indigenous person, associates indigenous people enrolled in Cadastro Único with the representation of poverty, and further reduces public actions to individual monetary transfers. These ideological and imagistic reductions should be the subject of critical reflection. In addition to the instrumental use of Cadastro Único and the information it produces, broader and more contextual meanings can be given to that information, especially by mobilizing the ideas of diversity and interculturality, a more appropriate interpretative framework for understanding the data. In this context, this Discussion Text presents Cadastro Único and the information regarding families and individuals from Indigenous Peoples contained therein. The central discussion permeates the description of the informative potential of this public policy instrument and its ability to coordinate strategies to guarantee different rights, based on the contexts of differentiated populations. The rights of Indigenous Peoples include self-determination and participation in the face of social rights, and therefore, in the deliberation on the methods of public action, respecting and providing subsidies that can determine paths for the implementation of public policies according to specific social, economic, and cultural situations.
Keywords: H5; Z18; 330; indigenous peoples; social rights; Single Registry of Social Programs (Cadastro Único); interculturality